2007
DOI: 10.1124/jpet.107.130914
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mechanisms Involved in the High-Dose and Long-Term Acetyl Salicylic Acid Therapy of Type I Diabetic Rats

Abstract: Diabetes mellitus has been classified as a conformational disease because of changes induced in the structure and function of proteins due to hyperglycemia. In this study, we investigated the effect of high-dose and long-term use of acetyl salicylic acid (ASA) on the streptozotocin-induced diabetic rats as a model of type I diabetes, with consideration on the structure and/or function of proteins. The N-[methylnitrosocarbamoyl]-D-glucosamine (streptozotocin)-induced diabetic rats together with the normal rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…More recent clinical studies report that T2-diabetic patients showed a 40 mg/dl decrease in fasting plasma glucose levels and a 21% reduction in blood glucose levels during a mixedmeal tolerance test after only 2 weeks of aspirin treatment [38]. Additionally, diabetic rodents treated with aspirin for a short term (7 days) or long-term (45 days to 5 months) regimes display significantly decreased blood glucose and HbA1c levels, similar to our findings [39,49,50]. In contrast, a small clinical study showed that neither aspirin treatment nor ibuprofen reduced fasting blood glucose levels in T2-diabetic patients, however this study had a small number of subjects compared to other studies, making their results difficult to draw conclusions from [54].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…More recent clinical studies report that T2-diabetic patients showed a 40 mg/dl decrease in fasting plasma glucose levels and a 21% reduction in blood glucose levels during a mixedmeal tolerance test after only 2 weeks of aspirin treatment [38]. Additionally, diabetic rodents treated with aspirin for a short term (7 days) or long-term (45 days to 5 months) regimes display significantly decreased blood glucose and HbA1c levels, similar to our findings [39,49,50]. In contrast, a small clinical study showed that neither aspirin treatment nor ibuprofen reduced fasting blood glucose levels in T2-diabetic patients, however this study had a small number of subjects compared to other studies, making their results difficult to draw conclusions from [54].…”
Section: Resultssupporting
confidence: 80%
“…A commonly used anti-inflammatory drug, aspirin, is known to reduce diabetes related inflammation [37,38] and decrease blood glucose levels in T1-diabetic rats [39]. Aspirin binds and inhibits cyclooxygenase (COX) enzyme and decreases prostaglandin (PG) production [40].…”
Section: Introductionmentioning
confidence: 99%
“…Both excessive and impaired HSP72 expression may disturb cell proliferation and function (Atalay et al 2009). Increased levels of HSP70 in human monocytes are observed in response to in vitro heat stress (Jafarnejad et al 2008;Vince et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…10) On one hand, there were studies suggesting that some non-steroidal anti-inflammatory drugs (NSAIDs) are effective in the treatment of type 1 diabetes, such as lisofylline (LSF), 11) pentoxifylline (PTX) 12) and aspirin. [13][14][15][16][17] Ibuprofen (IBU), also a NSAID, was reported to have the capacity of controlling blood glucose concentration and promoting glucose tolerance.…”
Section: Synthesis Of Diosgenin-ibuprofen Derivatives and Their Activmentioning
confidence: 99%
“…[13][14][15][16][17] Ibuprofen (IBU), also a NSAID, was reported to have the capacity of controlling blood glucose concentration and promoting glucose tolerance.…”
mentioning
confidence: 99%